2008
DOI: 10.1134/s1063783408090394
|View full text |Cite
|
Sign up to set email alerts
|

Self-quenching effects of excitons in CaWO4 under high density XUV free electron laser excitation

Abstract: Using free electron laser excitation in the XUV range, CaWO 4 samples were exposed to ultrashort intense photon pulses (photon energy, 89.84 eV; average pulse energy, 10 µ J; pulse length, 25 fs), and their luminescence was studied with time-resolved spectroscopy. In the decay curves measured in the temperature range 8-300 K, a nonexponential emission decay with shortening of the lifetimes over the first few microseconds was observed, depending on the excitation density. Using a model for dipole-dipole interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Comparing the three emission spectra measured for different average pulse energies, no significant changes in the structure of the bands were observed. This corresponds to similar findings in CaWO 4 and CdWO 4 [2] with the exception that in the case of CaWO 4 , a weak band of impurity-related defect emission at around 600 nm was observed. This defect band showed signs of saturation under higher pulse energies, which can easily be explained by the comparably low concentration of impurities in the crystal.…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…Comparing the three emission spectra measured for different average pulse energies, no significant changes in the structure of the bands were observed. This corresponds to similar findings in CaWO 4 and CdWO 4 [2] with the exception that in the case of CaWO 4 , a weak band of impurity-related defect emission at around 600 nm was observed. This defect band showed signs of saturation under higher pulse energies, which can easily be explained by the comparably low concentration of impurities in the crystal.…”
Section: Methodssupporting
confidence: 67%
“…The observed deviation from a single exponential decay behavior in the initial part of the decay curves in CaWO 4 and CdWO 4 under high excitation densities has been explained by the model of excitonic self-quenching [2][11]. The model is described in detail in these references, and will be only briefly introduced here.…”
Section: Self-quenching Of Excitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 are modelled using this theoretical approach. Quantitative results on the behaviour of different scintillators and luminescent materials under powerful FEL excitation will be presented in more detail elsewhere [10].…”
Section: Article In Pressmentioning
confidence: 99%
“…However, in insulators, where only a small radius of self-trapped excitons can be observed at room temperature, much higher densities of electronic excitations are required. Modern coherent sources of radiation such as free electron lasers, powerful tuneable amplified laser systems or those based on high-order harmonic generation are capable of creating electronic excitations at densities up to 10 21 cm 3 in about 10 −13 s. By using such sources the interaction of electronic excitations has been revealed in a sequence of wide band-gap crystals and a Förster theory based model has been developed for describing luminescence yield and decay kinetics in the conditions of crystal excitation by ultra-short high-intensity laser pulses [4][5][6]. However, recent experiments have shown that un-der the conditions of excitation by intense sub-picosecond monochromatic pulses the effective absorption coefficient of CsI crystals becomes dependent on pulse energy [7].…”
Section: Introductionmentioning
confidence: 99%